PIDATO 3 BAHASA (INDONESIA, ARAB, DAN INGGRIS) SEBAGAI METODE PEMBELAJARAN DAKWAH DI PONDOK PESANTREN MATHLA’UL ANWAR PONTIANAK - nanik shobikah (Jurnal Al-Hikmah: Jurnal Dakwah, 2018)
This study aims to describe the method of da'wah learning using the three-language speeches conducted by the Mathla'ul Anwar Islamic Boarding School in Pontianak as a flagship program to equip students with the ability to speak in three languages, namely Indonesian, Arabic and English. The results of the study showed that the method of da'wah learning using three language speeches was applied in muhadharah activities which were held every week on Saturday night. In this Muhadharah activity, the santri practice to give speeches in three languages. The santri were equipped with the ability to make speech texts, translated into Arabic and English and practiced speech in front of all the students at the Mathla'ul Anwar Islamic Boarding School in Pontianak City. (Penelitian ini bertujuan untuk mendeskripsikan metode pembelajaran dakwah menggunakan pidato tiga bahasa yang dilaksanakan oleh Pondok Pesantren Mathla’ul Anwar Kota Pontianak sebagai program unggulan untuk membekali para santrinya kemampuan untuk berpidato dalam tiga bahasa yaitu bahasa Indonesia, Arab dan Inggris. Hasil penelitian menunjukkan bahwa metode pembelajaran dakwah menggunakan pidato tiga bahasa diaplikasikan dalam kegiatan muhadharah yang dilaksanakan setiap minggu tepatnya hari Sabtu malam. Dalam kegiatan muhadharah ini, para santri berlatih untuk berpidato dalam tiga bahasa. Para santri dibekali kemampuan untuk membuat teks pidato, menterjemahkan kedalam bahasa Arab dan Inggris serta berlatih pidato didepan seluruh para santri di Pondok Pesantren Mathla’ul Anwar Kota Pontianak). Keywords: Speech, Three Languages, Dakwah (preaching) Learning Method